Degradation and release of tannic acid from an injectable tissue regeneration bead matrix in vivo. Issue 5 (14th December 2021) - Baldwin, Andrew; Hartl, Maximilian; Tschaikowsky, Mathaeus; Balzer, Bizan N.; Booth, Brian W.
Abstract: The development of multifunctional biomaterials as both tissue regeneration and drug delivery devices is currently a major focus in biomedical research. Tannic Acid (TA), a naturally occurring plant polyphenol, displays unique medicinal abilities as an antioxidant, an antibiotic, and as an anticancer agent. TA has applications in biomaterials acting as a crosslinker in polymer hydrogels improving thermal stability and mechanical properties. We have developed injectable cell seeded collagen beads crosslinked with TA for breast reconstruction and anticancer activity following lumpectomy. This study determined the longevity of the bead implants by establishing a degradation time line and TA release profile in vivo. Beads crosslinked with 0.1% TA and 1% TA were compared to observe the differences in TA concentration on degradation and release. We found collagen/TA beads degrade at similar rates in vivo, yet are resistant to complete degradation after 16 weeks. TA is released over time in vivo through diffusion and cellular activity. Changes in mechanical properties in collagen/TA beads before implantation to after 8 weeks in vivo also indicate loss of TA over a longer period of time. Elastic moduli decreased uniformly in both 0.1% and 1% TA beads. This study establishes that collagen/TA materials can act as a drug delivery system, rapidly releasing TA within the first week following implantation. However, the beads retain TA long term allowing them to resist degradation and remain in situ acting as a cell scaffold and tissue filler. This confirms its potential use as an anticancer and minimally invasive breast reconstructive device following lumpectomy.